2016
DOI: 10.1038/hdy.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

Like a pig out of water: seaborne spread of domestic pigs in Southern Italy and Sardinia during the Bronze and Iron Ages

Abstract: Southern Italy has a long history of human occupation and passage of different cultures since the Early Holocene. Repeated, ancient introductions of pigs in several geographic areas in Europe make it difficult to understand pig translocation and domestication in Italy. The archeozoological record may provide fundamental information on this, hence shedding light on peopling and on trading among different ancient cultures in the Mediterranean. Yet, because of the scanty nature of the fossil record, ancient remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The few pigs possessing an mt-Y1 signature from post-Neolithic contexts were found mostly on islands beyond mainland Europe in southwestern Greece (4,350 to 3,250 y BP: MM495, MM486, MM303), in Crete (3,100 y BP), in Sardinia (∼3,750 y BP) (29), near Naples (∼800 y BP: VM_CM01, VM_CM02, VM_CM03), and in Corsica (modern noncommercial pigs) (21), as well as in Tuscany (∼800 y BP: VM_TM01) (Fig. 1 and SI Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…The few pigs possessing an mt-Y1 signature from post-Neolithic contexts were found mostly on islands beyond mainland Europe in southwestern Greece (4,350 to 3,250 y BP: MM495, MM486, MM303), in Crete (3,100 y BP), in Sardinia (∼3,750 y BP) (29), near Naples (∼800 y BP: VM_CM01, VM_CM02, VM_CM03), and in Corsica (modern noncommercial pigs) (21), as well as in Tuscany (∼800 y BP: VM_TM01) (Fig. 1 and SI Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, furthering this research into Italian samples, Lega et al (2017) (Lega et al, 2017). This study thus offers additional support to the possibility of an independent pig domestication event in Italy.…”
Section: Genetic Studies On Pig Domesticationsupporting
confidence: 55%
“…In the particular case of Italy, the genetic evidence has offered support to the possibility of a local domestication of wild boar in the peninsula (e.g. Larson et al, 2007b;Lega et al, 2017;Vai et al, 2015). Hopefully, the research presented in this thesis and future developments will help decipher the picture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…through an Iberian intermediary) is also feasible. For instance, zoo-archaeological and molecular studies (mtDNA) conducted in the Sus genus, revealed that pigs were traded between the Italian Peninsula and Sardinia by the end of the second millennium BC (late Bronze age and Iron age) and this gene flow left a genetic signature still detectable in Sardinian feral pigs 25 . During the Bronze Age, the inhabitants of Sardinia were part of the Sea People, who migrated to the Levant at that time, with routes to Sicily and Crete 23 , 25 .…”
Section: Discussionmentioning
confidence: 99%